2015
DOI: 10.1007/s10393-015-1035-2
|View full text |Cite
|
Sign up to set email alerts
|

American Bullfrogs (Lithobates catesbeianus) Resist Infection by Multiple Isolates of Batrachochytrium dendrobatidis, Including One Implicated in Wild Mass Mortality

Abstract: The emerging amphibian disease chytridiomycosis varies in severity depending on host species.Within species, disease susceptibility can also be influenced by pathogen variation and environmental factors.Here, we report on experimental exposures of American bullfrogs (Lithobates catesbeianus) to three different isolates of Batrachochytrium dendrobatidis (Bd), including one implicated in causing mass mortality of wild American bullfrogs. Exposed frogs showed low infection prevalence, relatively low infection loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
6
24
0
1
Order By: Relevance
“…The infected individuals analyzed in this study showed no evident signs of chytridiomycosis, supporting the findings of Daszak et al (13) and eskew et al (26). Although the cycle threshold for positive results indicated moderate to minimal amounts of Bd DNA in the samples (23), bullfrogs become reservoirs and potential vectors of Bd to native cohabitant species.…”
Section: Abstract Bullfrogs Invasion Emerging Infectious Diseasessupporting
confidence: 88%
See 1 more Smart Citation
“…The infected individuals analyzed in this study showed no evident signs of chytridiomycosis, supporting the findings of Daszak et al (13) and eskew et al (26). Although the cycle threshold for positive results indicated moderate to minimal amounts of Bd DNA in the samples (23), bullfrogs become reservoirs and potential vectors of Bd to native cohabitant species.…”
Section: Abstract Bullfrogs Invasion Emerging Infectious Diseasessupporting
confidence: 88%
“…Experimental data show that L. catesbeianus is among the species capable of being infected by Bd without progression of clinical signs or death (13,26). The infected individuals analyzed in this study showed no evident signs of chytridiomycosis, supporting the findings of Daszak et al (13) and eskew et al (26).…”
Section: Abstract Bullfrogs Invasion Emerging Infectious Diseasessupporting
confidence: 86%
“…H. regilla and R. catesbeiana may have provided sufficient reservoir hosts to allow for Bd persistence in the system, facilitating chytridiomycosis-induced extinction of R. boylii. While some laboratory studies have suggested that bullfrogs may not always make suitable reservoir hosts for Bd(Eskew, Worth, Foley, & Todd, 2015;Gervasi et al, 2013), our observation that bullfrogs have the highest Bd prevalence and loads among species sampled in the field(Figure 7), and previous work showing that bullfrog sympatry is an important predictor of Bd infection in R. boylii(Adams et al, 2017), supports the hypothesis that bullfrogs are a vector of Bd in California, including where R. boylii are extant.Bullfrog farming may have played a key role in introducing and spreading Bd in California. Bullfrogs were brought to California in the early 20th century from the eastern United States, where Bd may have occurred in an enzootic state for much longer than in the western United States(Talley, Muletz, Vredenburg, Fleischer, & Lips, 2015).…”
supporting
confidence: 84%
“…boylii . While some laboratory studies have suggested that bullfrogs may not always make suitable reservoir hosts for Bd (Eskew, Worth, Foley, & Todd, ; Gervasi et al., ), our observation that bullfrogs have the highest Bd prevalence and loads among species sampled in the field (Figure ), and previous work showing that bullfrog sympatry is an important predictor of Bd infection in R . boylii (Adams et al., ), supports the hypothesis that bullfrogs are a vector of Bd in California, including where R .…”
Section: Discussionsupporting
confidence: 41%
“…There is little definitive evidence of species demonstrating widespread resistance to chytridiomycosis, but some species appear to demonstrate greater resistance than most, including the notorious invader Lithobates catesbeianus (Gervasi et al 2013;Eskew et al 2015), and threatened species in the genus Leiopelma (Bishop et al 2009;), amongst others (Woodhams et al 2007a;Gahl et al 2012;Searle et al 2011b). Furthermore, additional species are thought to be largely tolerant to infection, most notably the common laboratory species Xenopus laevis from Africa (Ramsey et al 2010;Van Rooij et al 2012), and…”
Section: Variation In Susceptibility To Chytridiomycosismentioning
confidence: 99%